Metaphors in Proverbs : Decoding the Language of Metaphor in the Book of Proverbs - Rotasperti, Sergio (Vetus Testamentum, Supplements, 2021)
Proverbs is a poetic book full of images and metaphors, many of which are often obscure and enigmatic. In this volume, Rotasperti offers a contribution to the understanding of figurative language in Proverbs by looking at the grammatical and social contexts in which many of the book's metaphors appear. The brief introduction explains the process and methodological assumptions used for identifying metaphors. The study then continues with a lexical review of four semantic categories: the body, urban fabric, nature and animals. The result of this survey is a deep analysis of several key metaphors that looks at their composition, structure, and interpretation.